Peran Orangtua dalam mendampingi Anak Belajar di Rumah pada Masa Pandemi Covid-19 - Nanang Sahriana; Raeh Niken Baghiroh Raeh; Silfa Saadatunnisa (JURNAL PENDIDIKAN DAN SAINS, 2022)
This research aims to provide an overview of parent’s role while accompanying children to learn from home during the Covid-19 pandemic. This research used library research with six stages namely: determining research topics, reviewing of literature up-to-date, reducing literature, organizing literature, review literature, and made conclusions. The data analysis technique in this research is descriptive qualitative. The current literature is the data sources used in this research , devided into two data sources , namely primary data sources including ebooks, international and national journals, and articles related to early childhood education and the covid-19 pandemic. The secondary data sources in this research was the latest news related to the covid-19 pandemic and early childhood. The result of this research indicate that the parent’s role while accompanying children to learn from home is proven to increase children’s achievement. Accompanying children to learn from home can build closeness between parents and children, be a good model for children, children feel not alone, parents as encouragement, prepare fasilities for children, establish intense communication with children, maintain religious values, develop children’s ability, create a conducive environment for learning, and provide freedom for children to learn and play. However, there are several obstacles faced by parents such as: difficulty in cultivating children’s interest in learning, difficulties in operating gadgets, not having enough time to accompany children, impatient parents in accompanying children, and obstacles related to internet service coverage